EPIDEMIOLOGICAL, CLINICAL, AND LABORATORY CHARACTERISTICS AND TREATMENT OUTCOMES OF SEVERE SEASONAL INFLUENZA IN CHILDREN TREATED AT THAI BINH PEDIATRIC HOSPITAL DURING THE PERIOD 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the epidemiological, clinical, laboratory characteristics, and treatment outcomes of children with severe seasonal influenza treated at Thai Binh Pediatric Hospital period 2024-2025.Subjects and methods: A descriptive study was conducted on 383 children with severe seasonal influenza. Comparisons were made between influenza A and influenza B, and the association of Oseltamivir use with fever duration and length of hospital stay was assessed.Results: The mean age was 2.75 ± 2.0 years, and 56.7% were male. Age-group distribution differed significantly between influenza A and B (p = 0.025). Cough was present in 100% of patients. Seizures were more frequent in influenza A than influenza B (23.9% vs 7.1%; p = 0.008). The influenza A group had higher white blood cell counts, platelet counts, and CRP levels. Recovery at discharge was 98.2%, with no deaths. Oseltamivir use was associated with shorter hospital stay and fever duration, especially when initiated within 48 hours.Conclusions: Influenza A predominated and was more associated with seizures, early Oseltamivir treatment improved clinical outcomes.
Keywords: Severe seasonal influenza, children, influenza A, influenza B, Oseltamivir.